2017
DOI: 10.1002/app.45279
|View full text |Cite
|
Sign up to set email alerts
|

A refined model for the mechanical properties of polymer composites with nanorods having different length distributions

Abstract: The aspect ratio of rod‐like nanofillers is an important factor that governs their percolation threshold in nanocomposites with a polymer of interest. Controlling the length distribution of a filler is an effective way to manipulate the onset of network formation and thereby materials properties that are related to the latter. The use of two or more different filler types with dissimilar aspect ratio is a special case to achieve such control. We here report the modification of an existing mechanical model to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Next to the connectivity range, there are many factors that influence the formation of transient networks in nanoparticle dispersions. A vast body of literature has shown that the particle anisometry, [15][16][17][18][19] size polydispersity, [13][14][15][19][20][21][22][23][24][25][26] the presence of nonconducting particles, [15] inter-particle interactions [27][28][29] and external fields [18,30] can have tremendous effects on the percolation threshold, while the influences of flexibility and the precise particle shape seem to be rather subtle. [27,31,32] In this article we focus on the fact that many types of conductive nanoparticle, like carbon nanotubes or graphene, have a strongly anisotropic shape, which strongly affects their interactions and the way they react to external orienting fields.…”
Section: Introductionmentioning
confidence: 99%
“…Next to the connectivity range, there are many factors that influence the formation of transient networks in nanoparticle dispersions. A vast body of literature has shown that the particle anisometry, [15][16][17][18][19] size polydispersity, [13][14][15][19][20][21][22][23][24][25][26] the presence of nonconducting particles, [15] inter-particle interactions [27][28][29] and external fields [18,30] can have tremendous effects on the percolation threshold, while the influences of flexibility and the precise particle shape seem to be rather subtle. [27,31,32] In this article we focus on the fact that many types of conductive nanoparticle, like carbon nanotubes or graphene, have a strongly anisotropic shape, which strongly affects their interactions and the way they react to external orienting fields.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites reinforced with hybrid carbon‐based fillers have received considerable attention in both scientific researches and industrial applications thanks to their unique electrical and mechanical properties, low weight, as well as low cost with easy processing . They are widely used in fields requiring conductive, mechanical, electrostatic dissipative, and electromagnetic shielding performances . Conductive particles are typically randomly distributed within an insulating substrate so that the entire composite material may be insulating or conductive; this depends on the electrical percolation threshold (EPT) , which is defined as a critical fiber volume fraction with a sharp onset of electrical conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…This limits its range of applications. Over the past 2 decades, there has been considerable progress in exploiting unique combinations of the electronic and mechanical properties of CNTs because of their excellent mechanical and physical properties . Extraordinarily, the EPT of CNTs is much lower compared with that of CB because of their high aspect ratio (over 1000) and high inherent conductivity (≤10 4 S/cm), which allows near‐ballistic electron transport in metallic CNTs with minimal scattering.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] DPD is a well-established coarse-grained simulation technique, which has proved extremely valuable in the prediction of the morphological evolutions of soft matter on larger time scales than that accessible by classic molecular dynamics. [35][36][37] The underlying principles of this method are described in details elsewhere and are not to be repeated here to preserve brevity. [33,[38][39][40] In order to represent a flexible polymer chain, several DPD beads were linked by finitely extensible nonlinear elastic (FENE) springs with the potential of ( ) 0.5 ln 1…”
Section: Microscopic Simulationsmentioning
confidence: 99%